This is your afterlife: gender, slavery, and televisual subjection. Issue 1 (2nd January 2017) - Haley, Sarah
Abstract : In 1957 Arries Ann Ward, who was formerly enslaved, appeared on the classic television interview-entertainment program, This Is Your Life. Despite Ward's practices of refusal, the rare interview enacts an idealization of black female servitude and indebted obligation through performances of affection and racial benevolence. Ward's appearance effectively works to resolve national crisis produced by widespread images of civil-rights protest and counterinsurgent violence, reifying discourses of American exceptionalism in Cold War context.